MANAJEMEN SEKOLAH BERPUSAT PADA SISWA UNTUK MENGUATKAN KEMANDIRIAN DAN DISIPLIN - Ami Laelatul Zuhri; Sari, Diana; Fitriana; Nadia Oktaviani; Rahmawati; Nirmatul Isnaeni; Muh.Fahrurrozi; Muhammad Sururuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the implementation of student-centered school management in strengthening elementary students’ independence and discipline. A descriptive qualitative case-study design was employed at SDN 2 Mamben Lauk, in Wanasaba, East Lombok. Data were collected through observations of school and classroom activities, interviews with the principal, classroom teacher, and fourth-grade students, and document analysis covering school regulations, classroom-duty schedules, habituation programs, activity photographs, and teacher evaluation notes. Data were analyzed through data condensation, display, and conclusion drawing, while source and method triangulation enhanced credibility. Four main patterns emerged. First, planning involved school rules, habituation programs, responsibility allocation, and monitoring mechanisms. Second, independence was fostered by allowing students to prepare learning materials, complete assignments, perform classroom duties, and assume age-appropriate responsibilities. Third, discipline was developed through teacher modeling, consistent rules, supportive supervision, and positive reinforcement. Fourth, routine evaluation enabled the school to adjust programs to students’ developmental needs. Implementation was constrained by diverse student characteristics, limited instructional time, and uneven parental support. The findings indicate that independence and discipline are strengthened when school management integrates student participation, consistent habituation, data-informed reflection, and sustained school–family support.